The headwinds An availability bias in assessments of barriers and blessings. [article]. - Davidai, Shai.
Seven studies provide evidence of an availability bias in people's assessments of the benefits they've enjoyed and the barriers they've faced. Barriers and hindrances command attention because they have to be overcome; benefits and resources can often be simply enjoyed and largely ignored. As a result of this "headwind/tailwind" asymmetry, Democrats and Republicans both claim that the electoral map works against them (Study 1), football fans take disproportionate note of the challenging games on their team's schedules (Study 2), people tend to believe that their parents have been harder on them than their siblings are willing to grant (Study 3), and academics think that they have a harder time with journal reviewers, grant panels, and tenure committees than members of other subdisciplines (Study 7). We show that these effects are the result of the enhanced availability of people's challenges and difficulties (Studies 4 and 5) and are not simply the result of self-serving attribution management (Studies 6 and 7). We also show that the greater salience of a person's headwinds can lead people to believe they have been treated unfairly and, as a consequence, more inclined to endorse morally questionable behavior (Study 7). Our discussion focuses on the implications of the headwind/tailwind asymmetry for a variety of ill-conceived policy decisions. -- (from the authors)
Keywords: Availability bias; Gratitude; Headwinds; Resentment; Tailwinds